Test study on failure and energy supply characteristics of rock under different loading stiffness. (December 2022) - Yin, Yanchun; Zheng, Wuwei; Tang, Xingxue; Xing, Minglu; Zhang, Yubao; Zhu, Yuanhui
Highlights: Authors develop several flexible rings with stiffness in the range of 0.07 ∼ 0.615GN/m, which provide an experimental means for the study of rock mechanics behaviors under different loading stiffness. This paper analyzes the stress–strain curves of rocks, and obtains the functional relationship between failure parameters and loading stiffness. Based on the test study of the influence of loading stiffness, this paper builds a rock burst model and explains the energy supply mechanism of rock burst quantitatively. Abstract: Based on the stiffness theory, the stiffness difference and energy supply of surrounding rocks are important inducing factors for rock burst. However, due to the lack of multi-level low stiffness testing machine, there are few experimental studies on rock failure mechanism under the influence of loading stiffness. Aiming at the above problems, this paper improved the rock mechanics testing machine, and developed several sets of low stiffness flexible rings, which realized laboratory test under five different loading stiffness in the range of 0.07 ∼ 0.615GN/m. Based on low stiffness loading device, the mechanical behavior of sandstone specimens was studied. With the decrease of the loading stiffness, the post-peak stage of the stress–strain curve of the specimen changes from step shape to oblique linear shape, and the specimen changes from progressive shear failure to brittle splitting failure. There is a power function positive correlation between the specimen's post-peak failure duration and stiffness ratio of the testing machine and the specimen, and a power function negative correlation between stress drop rate and stiffness ratio. When the specimen is damaged and the stress is dropped, the deformation of low stiffness testing machine rebounds with high-speed, resulting in an obvious dynamic load behavior. The loading stiffness has little effect on the energy storage and energy dissipation characteristics of the specimen, while the release energy of the testing machine increases as the stiffness ratio decreases, which is the key factor affecting the failure mode of the specimen. According to the test results, a rock burst mechanical model considering the stiffness is established, and the energy supply mechanism of rock burst is quantitatively explained.